2014
DOI: 10.3233/bme-140963
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of gallium and silver on Pseudomonas aeruginosa treated with gallium–silver–phosphate-based glasses

Abstract: Gallium and silver incorporated phosphate-based glasses were evaluated for antibacterial effect on the growth of Pseudomonas aeruginosa, which is a leading cause of opportunistic infections. The glasses were produced by conventional melt quenching methods at 1100 • C for 1 h. Glass degradation studies were conducted by weight loss method. Disc diffusion assay and cell viability assay displayed statistically significant (p 0.0005) effect on P. aeruginosa growth which increased with decreasing calcium content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Evaluation of antibacterial activity and anti-biofilm properties using P. aeruginosa . Combat infections Antibacterial activity and anti-biofilm formation [ 104 ] P 2 O 5 –MgO–CaO–Na 2 O–Ga 2 O 3 –CeO 2 , up to 7% CeO 2 or Ga 2 O 3 Characterization of glass by Raman, XRD, FTIR, In vitro degradation study in deionized water. In vitro cell viability evaluation using bone marrow stromal cells (ST2).…”
Section: Gallium In Bioactive Glassesmentioning
confidence: 99%
“…Evaluation of antibacterial activity and anti-biofilm properties using P. aeruginosa . Combat infections Antibacterial activity and anti-biofilm formation [ 104 ] P 2 O 5 –MgO–CaO–Na 2 O–Ga 2 O 3 –CeO 2 , up to 7% CeO 2 or Ga 2 O 3 Characterization of glass by Raman, XRD, FTIR, In vitro degradation study in deionized water. In vitro cell viability evaluation using bone marrow stromal cells (ST2).…”
Section: Gallium In Bioactive Glassesmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the effective antibiofilm activity of different formulations of BGs. Ag + , Cu 2+/+ , Ga 3+ , Ti 4+ , and Zn 2 + are some examples of ions that can be used in doped BGs to target the inhibition and disruption of bacterial biofilm [ 47 , 48 , 50 , 53 ].…”
Section: Metal Ions Incorporated Bioactive Glasses With Antibiofilm E...mentioning
confidence: 99%
“…According to the study [ 47 ], melt-derived Ag- and Ga-doped phosphate glass with the following composition 10CaO-37Na 2 O-45P 2 O 5 -3Ga 2 O 3 -5Ag 2 O (mol %) contributed to the biofilm growth inhibitory effect on P. aeruginosa (up to 2.68 reductions in log10 values of the viable counts compared with controls). The composition may offer a successful choice to combat opportunistic pathogens such as P. aeruginosa -associated infections due to the controlled release of antibacterial Ga and Ag ions at the site of infection.…”
Section: Metal Ions Incorporated Bioactive Glasses With Antibiofilm E...mentioning
confidence: 99%
“…In general, gallium has been tested at concentrations between 1 and 8% mol of Ga 2 O 3 . Phosphate‐based glasses have shown good antibacterial effect against a broad spectrum of planktonic bacterial pathogens and some biofilms (Valappil and Higham ; Valappil et al . ).…”
Section: Bioactive Glasses As Biomaterials Delivery Systems For Antimimentioning
confidence: 99%
“…Also, decreasing the calcium content in gallium–Ag–phosphate‐based glasses increases their antibacterial properties (Valappil and Higham ). These glasses have been found to deliver gallium and Ag in a controlled way and to exert cumulative antibacterial action on planktonic and biofilm growth of P. aeruginosa (Valappil and Higham ) and biofilm of oral human pathogens (Valappil et al . ).…”
Section: Bioactive Glasses As Biomaterials Delivery Systems For Antimimentioning
confidence: 99%